Crazy Ant, Paratrechina longicornis (Latreille) (Insecta: Hymenoptera: Formicidae) - J. C. Nickerson; Kathryn A. Barbara (EDIS, 2003)
Crazy ants, Paratrechina longicornis (Latreille), occurs in large numbers in homes or outdoors. They often forage long distances away from their nests, so nests are often difficult to control. The name "crazy ant" arises from its characteristic erratic and rapid movement not following trails as often as other ants. The crazy ant is so morphologically distinctive that it is one of the few Paratrechina that is not consistently misidentified in collections (Trager 1984). This document is EENY-142, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2000.